The Influence of Human Resources Audit on Employee Job Satisfaction (A Case Study at PT. Bank Pembangunan Daerah West Java and Banten, Tbk (BJB) Central Office Bandung) - Hawa Az-Zahra Kifayah; Syakieb Arsalan (UNIVED Press, 2024)
The main purpose of this paper is to identify how HR audits affected job satisfaction. In this study, 52 participants were surveyed and analyzed using a quantitative descriptive analysis technique. A questionnaire served as the instrument for gathering information, and SPSS 25 was used for analysis, specifically the multiple linear regression technique. The hypothesis that